2018
DOI: 10.4236/ce.2018.914171
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Framework of Quality Product Design Based on Computer Aided Design (CAD)

Abstract: Producing a sustainable product quality and innovation ecosystem is not an easy thing, especially in the product development stage. Therefore, Computer-Aided Design (CAD) software can be utilized as an important tool to develop the creative design and quality product. This paper discussed the conception of quality design for the production of product design. This study employed systematic review of producing a conceptual framework to examine the systematic development process of product design quality with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This aspect of information technology also makes students' ideas and creativity to be more productive (Iyendo & Alibaba, 2015). Cenani and Aksoy (2020) (Oladumiye, Hassan, & Adelabu, 2018); Zobo Tea Package Design Prototype Allied with Product Onomastics (Oluyemi, Oladumiye, & Adelabu, 2021) (Fakhritdinovna, 2021); The Conceptual Framework of Quality Product Design Based on Computer Aided Design (CAD) by Saleh, Rasul, & Affandi (2018) and to mention a few. The fact is that there are a lot of studies on computer application among which CAD is confirmed to have enhanced students' creative behaviour and more CAD related courses are expected to be integrated into the curricula of tertiary institutions (Oladumiye et al, 2018).…”
Section: The Use Of Computer Aided Design (Cad) In Studio Practicementioning
confidence: 99%
“…This aspect of information technology also makes students' ideas and creativity to be more productive (Iyendo & Alibaba, 2015). Cenani and Aksoy (2020) (Oladumiye, Hassan, & Adelabu, 2018); Zobo Tea Package Design Prototype Allied with Product Onomastics (Oluyemi, Oladumiye, & Adelabu, 2021) (Fakhritdinovna, 2021); The Conceptual Framework of Quality Product Design Based on Computer Aided Design (CAD) by Saleh, Rasul, & Affandi (2018) and to mention a few. The fact is that there are a lot of studies on computer application among which CAD is confirmed to have enhanced students' creative behaviour and more CAD related courses are expected to be integrated into the curricula of tertiary institutions (Oladumiye et al, 2018).…”
Section: The Use Of Computer Aided Design (Cad) In Studio Practicementioning
confidence: 99%
“…These industrial parks link different but interrelated technological and innovative sectors that determine the success or failure of new products. These sectors include research and development, investment, pricing, quality control and environmental protection [9].…”
Section: Few Industrial Parksmentioning
confidence: 99%